Mycobiome Composition and Diversity under the Long-Term Application of Spent Mushroom Substrate and Chicken Manure - Magdalena Frąc; Giorgia Pertile; Jacek Panek; Agata Gryta; Karolina Oszust; Jerzy Lipiec; Bogusław Usowicz (Agronomy, 2021)
Waste exogenous organic matter, including spent mushroom substrate (SMS) and chicken manure (CM), can be used as the basis of a soil-improving cropping system in sustainable agriculture. However, there is—as yet—a lack of information about important quality indicators such as the fungal community relative abundance, structure and biodiversity in soils treated with these additives. In this study, the responses of the soil fungal community composition and mycobiome diversity to SMS and CM application compared to the control soil were evaluated using a combination of the following molecular approaches: quantitative polymerase chain reactions, denaturing gradient gel electrophoresis, terminal restriction fragment length polymorphism, and next-generation sequencing. The most abundant phylum for both treatments was Ascomycota, followed by Basidiomycota. The application of SMS and CM increased the abundance of fungi, including Tremellomycetes and Pezizomycetes for the SMS additive, while the Mortierellomycetes, Pezizomycetes, and Leotiomycetes levels increased after CM addition. SMS and CM beneficially reduced the relative abundance of several operational taxonomic units (OTUs) which are potential crop pathogens. The results provide a novel insight into the fungal community associated with organic additives, which should be beneficial in the task of managing the soil mycobiome as well as crop protection and productivity.